PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBAHASA INGGRIS YANG BERORIENTASI PEMETAAN PIKIRAN MENGGUNAKAN APLIKASI iMindMap PADA MATERI STRUKTUR JARINGAN HEWAN - RIZQI AMALIA, ALFI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The objective of this research was to produce worthy worksheet in English which was oriented with mind mapping using iMindMap application on the material of animal tissue structure. This research was done using Fenrich instructional development cycle model. The research result showed that the average value of validation from two biology lectures, a biology teacher, a linguist, and a computer expert towards the student’s worksheet was about 92,81%. The percentage of student’s value to make mind map using iMindMap application was about 86,67%. Most students gave positive response towards the student’s worksheet which was developed, so the student’s worksheet was worthy to be used with very good category. Keywords: student’s worksheet, mind map, iMindMap, animal tissue